2012
DOI: 10.1017/s1751731111002229
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality, testosterone, seminal plasma biochemical and antioxidant profiles of rabbit bucks fed diets supplemented with different concentrations of soybean lecithin

Abstract: A total of 28 adult V-line rabbits were fedad libituma control diet or a diet supplemented with 0.5%, 1.0% and 1.5% soybean lecithin (SL) for 12 weeks. Bucks that received 0.5%, 1.0% or 1.5% dietary SL had a higher ejaculate volume, mass motility, sperm concentration, total sperm output and total motile sperm. Dietary SL reduced the percentage of dead sperm and increased the normal sperm, and this concurred with an increase in blood testosterone concentration. Blood and semin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 50 publications
3
29
0
2
Order By: Relevance
“…Semen was collected weekly from all bucks at 28 weeks of age and continued for 16 weeks to determine semen quality, according to and Attia and Kamel (2012). Semen collection was carried out using artificial vagina.…”
Section: Diet Nutrient Profilesmentioning
confidence: 99%
“…Semen was collected weekly from all bucks at 28 weeks of age and continued for 16 weeks to determine semen quality, according to and Attia and Kamel (2012). Semen collection was carried out using artificial vagina.…”
Section: Diet Nutrient Profilesmentioning
confidence: 99%
“…Okab et al (2007) reported that the leakage of ALP and LDH in rabbit seminal plasma during summer and spring, respectively, could reveal a positive correlation between enzyme release and sperm cell integrity and acrosomal damage. In other works in rabbit, enzyme activity in seminal plasma has been studied to evaluate the effect of diet supplementation with different substances on semen quality (Yousef, 2005, Yousef et al, 2003, 2010Attia and Kamel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of triglycerides, total lipids and phospholipids in the blood were found in animals fed diets with SL addition which as an emulsifier increases fat absorption in the gut (Attia et al, 2009;Attia and Kamel, 2012). In addition, triglyceride levels were also dependent on the level of hepatic lipogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…SL improves the productive and reproductive performance of laying hens and rabbit bucks and is a good source of unsaturated fatty acids, antioxidants and energy (Attia et al, 2009;Attia and Kamel, 2012). PC from biliary sources increased lymphatic triglyceride absorption in Wistar rats which might be connected with the packaging and secretion of chylomicrons (Nishimukai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%